Size and value effects in equity hedge funds. (28th October 2016) - Kim, Jung-Min
ABSTRACT: Contrary to the findings in mutual funds, both size and value effects appear in equity hedge funds. Small-cap/value funds outperform large-cap/growth funds. Both asset and share liquidity measures show that small-cap/value funds manage less liquid assets and are more likely to have lockup restrictions than large-cap/growth funds. Furthermore, small-cap/value funds earn more benefits from using lockups than large-cap/growth funds. In part, lockups are helpful for small-cap/value funds by mitigating a fire-sale risk during crisis periods.